Targeting Warburg effect to rescue the suffocated photodynamic therapy: A cancer-specific solution. (March 2023) - Su, Yaoquan; Lu, Keqiang; Huang, Yuhang; Zhang, Jingyu; Sun, Xiaolian; Peng, Juanjuan; Zhou, Yunyun; Zhao, Lingzhi
Abstract: The cancer photodynamic therapy (PDT) is limited by a congenital defect, namely the tumor hypoxia. Cancer cells are characterized by the vigorous oxygen-consuming glycolysis, which is well-known as the "Warburg effect" and one of the primary causes for the hypoxia. Herein, we employed the glucose metabolism as the cancer-specific target to enhance the performance of PDT. The Salvianolic acid B as the inhibitor of glucose uptake and aerobic glycolysis was concomitantly delivered with the photosensitizer chlorin e6 by a redox-responsive organosilica cross-linked micelle. The results demonstrated that the Salvianolic acid B suppressed the glucose metabolism, retarded the oxygen consumption to retain adequate oxygen as the ammo for PDT, which remarkably improve the efficacy of PDT both in vitro and in vivo. Our study not only provides an alternative strategy to address the hypoxia problem for PDT, but also enhances the selectivity of the treatment by targeting the cancer-specific Warburg effect.